Interfaith Harmony and Maulana Zafar Ali Khan - Shazia Razzak (بازیافت, 2019)
Molana Zafar Ali Khan marked his presence in the political, social, literary, historical and cultural life of his age, which was indeed a difficult and sensitive era. He was an institute in his own personality and leader of a depressed community. Allama Shibli Naumani was proud of him as his student. Unity among Muslims was the main objective of his life. He was messenger of love, affection and religious tolerance and these concepts reveals from his newspaper "Zameendaar". The legacy developed through saints and their teachings in united India and religious tolerance taught by them could be seen in prose and poetry of Molana Zafar Ali Khan. My article is an attempt to search the aforesaid concepts of Interfaith tolerance, peace and also to describe Molana's love and respect for Islam